Production systems and methods affect the quality and the quantity of saffron (Crocus sativus L.) - Aghhavani-Shajari, Mahsa; Fallahi, Hamid-Reza; Sahabi, Hossein; Kaveh, Hamed; Branca, Ferdinando (Spanish Journal of Agricultural Research, 2021)
Aim of study: Comparison of saffron flowering between open field and controlled environment. Possibility of saffron transplanting.Area of study: University of Birjand (Iran)Material and methods: In a first experiment, saffron yield and quality produced by traditional production system (TPS) and by soilless one (SPS) were compared. In a second experiment, the effects of the production method, by direct planting (DP) or by transplanting plant (TP) in open field were studied.Main results: Percentage of flowering corms grown by SPS was 39% and 65%, while by TPS was 6% and 56% in 2018 and 2019, respectively. Flower and stigma yields were significantly higher by SPS than by TPS. Stigma obtained from SPS had higher L (lightness) and crocin. Safranal content was higher in stigma produced by TPS. Leaf and root numbers and corm weight were higher for SPS, but after transplanting there was better status for DP than for TP. At the end of the first growing season (2018-19), mean replacement corms weight (4.4 vs 3.0 g), replacement corms yield (21.3 vs 12.8 g per plant), weight of main replacement corm (11.7 vs 6.0 g) and number of large replacement corms (0.6 vs 0.1 corms per plant) for DP were significantly higher than for TP. However, during the second growing season (2019-20), the plants in TP plots improved their performances.Research highlights: Saffron production was more favorable under controlled environment. Transplanting is possible, but there is a need to improve methods to gain more favorable results.